Short-acting β-agonist use as a marker of current asthma control - Patel, Mitesh; Pilcher, Janine; Munro, Claire; Hosking, Alexander; Pritchard, Alison; Shaw, Dominick; Black, Peter; Weatherall, Mark; Beasley, Richard (Elsevier, 2013)
Background